Front Cover: Solvated Actinoids: Methanol, Ethanol, and Water Adducts of Thorium and Uranium Tetrachloride (Eur. J. Inorg. Chem. 21/2022). Issue 21 (30th June 2022) - Kasperowicz, Thomas; Flosbach, Niko T.; Grödler, Dennis; Kasperowicz, Hannah; Neudörfl, Jörg‐M.; Rennebaum, Tobias; Wickleder, Mathias S.; Zegke, Markus
Abstract : The Front Cover shows that there are occasions on which chemistry shows its human face. Thorium(IV) and uranium(IV), both of which share a love for chloride, saturate themselves quite literally when given the opportunity to take up some alcohol or water, i.e. polar‐protic solvents. When either ThCl4 or UCl4 is treated with methanol or ethanol, the molecular solvent adducts [ThCl4 (MeOH)4 ], [UCl4 (MeOH)4 ], [ThCl4 (EtOH)4 ] and [UCl4 (EtOH)4 ] form. The tendency to form the water adduct is so strong that, when a Th adduct is dissolved in hydrochloric acid, two Th−Cl bonds break up and [ThCl2 (H2 O)7 ](Cl)2 (H2 O)2, which is isotypic with the already known [UCl2 (H2 O)7 ](Cl)2 (H2 O)2, forms. At elevated temperature, the materials decompose to form their respective oxides. More information can be found in the Research Article by M. Zegke and co‐workers .